PSYCHOANALYTICAL VIEWS IN CROSS-CULTURAL COUNSELING AND HOW TO ELIMINATE CULTURAL BIAS IN STUDENTS - Hasugian, Tesalonika; Putriyani, Imelda; Ortis Gultom, Yosia; Khopsah, Khopsah (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
Psychoanalysis is a theory developed by Sigmund Freud where it is said that past experiences affect a person in the present. In this theory Sigmund divides the level of consciousness into three namely id, ego and superego. In cross-cultural counseling, psychoanalysis looks at the background of the emergence of individual behavior based on their past. In this day and age, there are many problems related to cultural bias, one of which is on students. Indonesian culture that is diverse and thick and thick in the life and daily life of Indonesian people makes cultural biases happen to anyone, including students. Many of the people in Indonesia who are known for their cultural bias are people who have been implanted with cross-cultural views since their time as students. Therefore, psychoanalysis as a science that studies the past and matters related to the past is expected to be able to eliminate cultural biases in students. So that in the future so that culture does not look bad at other cultures.